Improving Decision Making for Transportation Capacity Expansion: Qualitative Analysis of Best Practices for Regional Transportation Plans. Issue 1 (2016) - Ewing, Reid; Proffitt, David
The need for innovative regional transportation planning has grown as metropolitan areas consider the impact of congestion reduction efforts on induced demand, public health, and fossil fuel use and climate change. Although conventional practice among metropolitan planning organizations (MPOs) is to simply expand roadway capacity to relieve congestion, many MPOs have also developed new solutions. This study qualitatively analyzes a national sample of 38 regional transportation plans to identify best practices among MPOs for increasing the capacity of regional transportation networks without inducing additional traffic or unnecessary emissions. It focuses on real-world examples of innovative practices such as the use of high-occupancy toll lanes on major freeways, regulations and ordinances designed to improve the connectivity of minor streets, management of transit corridors, and the best locations for bicycle and pedestrian infrastructure.